Brief Report: Associations Between Self-Reported Paternal Relationships, Anger, Alcohol, and Intimate Partner Violence in a Prison Sample. (July 2017) - Bernardi, Jessica; Day, Andrew; Bowen, Erica
This study investigates the association between family relationships, anger, alcohol use, and self-reported intimate partner violence (IPV). Participants were 55 male prisoners who completed a survey about their family relationships, anger, alcohol use, and aggression. Exposure to parental IPV predicted rates of self-reported perpetration of IPV, suggesting the importance of understanding more about the developmental pathways to IPV if effective prevention, intervention, and assessment strategies are to be developed for use with this high-risk population.